Fabric and tensile structure: the suitability in Malaysia climate / Mohd. Khazani Samat @ Darawi - Samat @ Darawi, Mohd. Khazani (2007)
This dissertation is a study to find out the advantages and disadvantages of using tensile structure in Malaysia as a tropical country. The strengths and weakness of the system have been identified, regardless of whether it is a small or big scale structure. Fabric, tensile and membrane structures can be developed and exploited in a wide variety of tensile based systems. A tension structure may be fabricated as a permanent or temporary structure for commercial or residential use, public assembly tent structures, temporary event structures, modular industrial construction and landscape artwork. Tensile structure shade canopy is typically used as a lightweight roof, protective cover, shelter, skylight, advertisement and/or identification for stadiums, arenas, shopping malls, amphitheaters, band shell, stage cover, tents, and shade structures for airport and transportation depots. The attributes of tensile membrane structures can be developed and exploited in a wide variety of tensile based systems, provided that there are proper maintenance and right materials. Observation on the structures and the materials, interview with regular users had revealed the disadvantages. The beautiful designs now no longer look good because of the faded and dull tensile structures.